2020
DOI: 10.1364/ao.383454
|View full text |Cite
|
Sign up to set email alerts
|

Microlens testing on back-illuminated image sensors for space applications

Abstract: The optoelectronic properties of image sensors, among which are the photosensitivity and resolution, are key to the quality factors for imaging as well as spectrometry in Earth observation and scientific space exploration missions. Microlens arrays (MLAs) further improve state-of-the-art CMOS image sensors (CIS) by redirecting more photons into the photosensitive surface/volume of each pixel. This paper reports the design, deposition, optical characterization, and reliability assessment of such an MLA made fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Refractive microlens structures were manufactured using an improved process flow based on UV-replication (or UVimprinting) [4], [11], [12] . Photoresist masters are used to fabricate molds for imprints of UV curable hybrid polymers deposited on top of the SPAD arrays.…”
Section: Methodsmentioning
confidence: 99%
“…Refractive microlens structures were manufactured using an improved process flow based on UV-replication (or UVimprinting) [4], [11], [12] . Photoresist masters are used to fabricate molds for imprints of UV curable hybrid polymers deposited on top of the SPAD arrays.…”
Section: Methodsmentioning
confidence: 99%
“…Using the converging effect of MLAs on light, it can be coupled with a CCD and CMOS to improve the luminous sensitivity of the sensors, thus improving their pixel quantum efficiency. [157] As early as the 1990s, Deguchi et al used a MLA to improve the imaging performance of the CCD. [158] The experimental results showed that the sensitivity of the CCD was improved three times compared to the CCD without coupling MLA.…”
Section: Sensingmentioning
confidence: 99%
“…Zanella et al fabricated microlens from a UV-curable polymer and replicated them on a back-illuminated CMOS image sensor (BI-CIS) with 2048 × 256 pixels on a 15.5 µm square pitch. [46] Compared to the pixels covered with microlens material, the microlens had greatly improved the performance of the BI-CIS. The average value of MTF increased from 0.577 to 0.594, QE increased from 83.1% to 85.7% (the spectrum from 400 to 700 nm), and 1/PLS increased from 565 to 1043 at the wavelength of 800 nm.…”
Section: Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Microlens arrays (MLAs) and MLA-based artificial compound eyes (ACEs) play a key role in advanced micro-optical systems (Pan et al, 2007 ; Song et al, 2013 ; Gorzelak et al, 2014 ; Petsch et al, 2016 ; Lin et al, 2018 ). By taking advantages of small size, high integration, and striking optical capability, MLAs and ACEs are widely applied in light-field regulation (Deng et al, 2014 ; Wei et al, 2018 ; Zhou et al, 2018 ; Sohna et al, 2019 ), fiber coupling (Elsherif et al, 2019 ; Liu et al, 2019 ; Orth et al, 2019 ), lab-on-chip devices (Fei et al, 2011 ; Lv et al, 2016 ; Vespini et al, 2016 ), biochemical observation (Ma et al, 2014 ; Holzner et al, 2018 ), laser microfabrication (Bekesi et al, 2010 ; Li et al, 2020 ), solar cells (Chen Y. et al, 2013 ), sensors (Zanella et al, 2020 ), three-dimensional imaging (Li et al, 2016 ; Kim et al, 2019 ; Zhang et al, 2019 ; Joo et al, 2020 ; Qin et al, 2020 ; Zhao et al, 2020 ), and light extraction (Shin et al, 2018 ; Zhou et al, 2019a , b ). However, the normal use of the MLA is usually restricted by many limitations.…”
Section: Introductionmentioning
confidence: 99%